Improving Critical Thinking Skills using Problem Based Learning: Systematic Literature Review - Era Mutiara; Slamet Suyanto; Nur Khafifah Luthfiyah B; Ghany Desti Laksita; Zamzami Zamzami (Jurnal Penelitian Pendidikan IPA, 2024)
Enhancing critical thinking skills is a valuable learning asset in the twenty-first century, and utilizing an educational framework that promotes this development can aid students' growth. Research reveals problem-based learning as the sole form of instruction most effective at fostering critical thinking abilities among pupils. In light of these findings, this study examines articles from Sinta-indexed journals to evaluate research on PBL models regarding their impact on promoting critical thought processes. The purpose of this paper is to provide a comprehensive overview of reputable publications released within the last five years (2020-2024), highlighting how PBL strategies assist learners in cultivating crucial analytic capabilities. The primary focus of this study is data on critical thinking abilities and problem-based learning models in the fields of science, biology, chemistry, physics, and mathematics. This research used the PRISMA approach, a literature study methodology consisting of four parts (identification, screening, feasibility, and inclusion). It is found through identification, screening, and eligibility there are 12 articles collected from various journal publishers and hundreds of journal articles. The study's conclusions indicate that most research on PBL models and critical thinking abilities is carried out in Indonesia at different educational levels. Scientific research frequently makes use of experimental procedures. Furthermore, it was shown that PBL research encompasses more traits than only critical thinking abilities. The examination of current publications makes it clear that the PBL technique can promote critical thinking abilities.